1984
DOI: 10.1002/j.1552-4604.1984.tb01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxyethyl Starch and Dextran on Plasma Volume and Blood Hemostasis and Coagulation

Abstract: Six healthy male subjects were given in a crossover fashion medium molecular weight (HES 125) and low molecular weight (HES 40) hydroxyethyl starch, dextran, and balanced salt solution by intravenous infusion. The plasma volumes were determined using labeled albumin and plasma protein measurements. Three properties of factor VIII protein complex and indices of blood coagulation and hemostasis were measured before and after the infusions. Both the salt solution and HES 40 increased plasma volume, but their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 18 publications
2
16
0
2
Order By: Relevance
“…Intraoperative blood Blood loss in the Additional blood loss Additional blood loss loss, ml recovery room, ml until first postoperative until first postoperative morning, ml evening, ml ALBn =481 400 (400-3500) 1000 (200-2600) 300 (0-1100) 100 (0-570) HES n=53 1200 (400-8300) 1150 (300-3400) 300 (0-1000) 150 (0-600) The findings concerning HES in the present study are in accordance with a previous study in volunteers where a small dose of a low molecular weight HES (125 kDa) with high substitution ratio (0.7) caused no, or only minimal changes in blood coagulation (13). However, had a larger dose of HES had been given, a decrease in coagulation factor levels might have been seen (14).…”
Section: Groupsupporting
confidence: 91%
“…Intraoperative blood Blood loss in the Additional blood loss Additional blood loss loss, ml recovery room, ml until first postoperative until first postoperative morning, ml evening, ml ALBn =481 400 (400-3500) 1000 (200-2600) 300 (0-1100) 100 (0-570) HES n=53 1200 (400-8300) 1150 (300-3400) 300 (0-1000) 150 (0-600) The findings concerning HES in the present study are in accordance with a previous study in volunteers where a small dose of a low molecular weight HES (125 kDa) with high substitution ratio (0.7) caused no, or only minimal changes in blood coagulation (13). However, had a larger dose of HES had been given, a decrease in coagulation factor levels might have been seen (14).…”
Section: Groupsupporting
confidence: 91%
“…Previous studies have reported a reduction in cerebral infarct size with the use of these agents 8,12) and improvement in cerebral blood flow in ischemic as well as normal brain 6,19) . Although the etiology Coagulopathy with the Use of Hydroxyethyl Starch|SH Hwang, et al of this improvement was unclear, they suggested theories including hemodilution, decreased plasma viscosity, increased cardiac output, or mild elevation of clotting time 7,12,20) . The mild elevation of clotting time was ascribed to precipitation by hetastarch of factor VIII 5,7,10,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology Coagulopathy with the Use of Hydroxyethyl Starch|SH Hwang, et al of this improvement was unclear, they suggested theories including hemodilution, decreased plasma viscosity, increased cardiac output, or mild elevation of clotting time 7,12,20) . The mild elevation of clotting time was ascribed to precipitation by hetastarch of factor VIII 5,7,10,15) . Studies in humans used doses lower than those necessary for the treatment of vasospasm in normal volunteers 8,15) .…”
Section: Discussionmentioning
confidence: 99%
“…wt. 70000) infusion [13]. The hemodynamic effects of hetastarch have been found to be comparable to those of a 5% albumin solution [14,32].…”
Section: Introductionmentioning
confidence: 92%
“…Hetastarch seems to cause only minor changes in laboratory parameters; it is nontoxic and nonallergenic in doses of up to 6 g/kg in dogs [14]. However, in excessive doses hetastarch has been found to decrease factor VIII values and it produces prolongation of the bleeding time [5,13]. The frequency of severe anaphylactoid reactions has been 0.006% for hetastarch [29].…”
Section: Introductionmentioning
confidence: 97%